Symptoms of stress and coping strategies in Mozambican higher education teachers (Research, Society and Development, 2021)
Teaching has been considered highly stressful in the face of the various challenges related to your profession. This work aims to evaluate the symptoms of stress and coping strategies in university professors from a public institution of higher education in Mozambique. The research is quantitative, descriptive and had a sample of 100 teachers, 58% of whom were male and 42% female. Data collection took place using three instruments: Lipp's Stress Symptom Inventory for Adults (ISSL-Lipp), short version of Coping Orientation to Problems Experienced Inventory (Brief-COPE), and the questionnaire on socio-demographic and labor data. Statistical analysis of the data with the help of SPSS indicated that most of the teachers surveyed showed symptoms of stress in the alert and resistance phase, with a predominance of psychological symptoms. And in stressful situations, teachers recommend the use of coping strategies focused on the problem and emotion. The need for future studies to identify the consequences and sources of occupational stress in teachers is highlighted, in order to propose more appropriate prevention and intervention strategies.